Veblenite, K2_2Na(Fe2+5 Fe3+4 Mn2+7_)Nb3Ti(Si2O7)2 (Si8O22)2O6(OH)10(H2O)3, a new mineral from Seal Lake, Newfoundland and Labrador: mineral description, crystal structure, and a new veblenite (Si8O22) ribbon - CAMARA ARTIGAS, Fernando; Sokolova E; Hawthorne FC; Rowe R; Grice JD; Tait KT (Mineralogical Magazine, 2013)
Veblenite, ideally K2_2Na(Fe2+5 Fe3+4 Mn2+7 _)Nb3Ti(Si2O7)2(Si8O22)2O6(OH)10(H2O)3, is a new mineral with no natural or synthetic analogues. The mineral occurs at Ten Mile Lake, Seal Lake area, Newfoundland and Labrador (Canada), in a band of paragneiss consisting chiefly of albite and arfvedsonite. Veblenite occurs as red brown single laths and fibres included in feldspar. Associated minerals are niobophyllite, albite, arfvedsonite, aegirine-augite, barylite, eudidymite, neptunite, Mnrich pectolite, pyrochlore, sphalerite and galena. Veblenite has perfect cleavage on {001} and splintery fracture. Its calculated density is 3.046 g cm3. Veblenite is biaxial negative with alpha 1.676(2), beta 1.688(2), gamma 1.692(2) (l 590 nm), 2Vmeas = 65(1)º, 2Vcalc = 59.6º, with no discernible dispersion. It is pleochroic in the following pattern: X = black, Y = black, Z = orange-brown. The mineral is red-brown with a vitreous, translucent lustre and very pale brown streak. It does not fluoresce under short and long-wave UV-light. Veblenite is triclicnic, space group P¯ 1, a 5.3761(3), b 27.5062(11), c 18.6972(9) A˚, alpha 140.301(3), beta 93.033(3), gamma 95.664(3)º, V = 1720.96(14) A˚^3. The strongest lines in the X-ray powder diffraction pattern [d(A˚ )(I)(hkl)] are: 16.894(100)(010), 18.204(23)(01¯ 1), 4.271(9)(14¯ 1, 040,120), 11.661(8)(001), 2.721(3)(19¯5), 4.404(3)(1¯3¯ 2, 14¯ 2), 4.056(3)(031, 11¯ 2; 15¯ 2, 1¯ 4¯ 3), 3.891(2)(003). The chemical composition of veblenite from a combination of electron microprobe analysis and structural determination for H2O and the Fe2+/Fe3+ ratio is Nb2O5 11.69, TiO2 2.26, SiO2 35.71, Al2O3 0.60, Fe2O3 10.40, FeO 11.58, MnO 12.84, ZnO 0.36, MgO 0.08, BaO 1.31, SrO 0.09, CaO 1.49, Cs2O 0.30, K2O 1.78, Na2O 0.68, H2O 4.39, F 0.22, O = F 0.09, sum 95.69 wt.%. The empirical formula [based on 20 (Al+Si) p.f.u. is (K0.53Ba0.28Sr0.03_0.16)Sisgma1(K0.72Cs0.07_1.21)S2(Na0.72Ca0.17_1.11)Sigma2 (Fe2+5.32Fe3+4.13Mn2+5.97Ca0.70Zn0.15Mg0.07_0.66)Sigma17 (Nb2.90Ti0.93Fe3+0.17)Sigma4 ...